Environmental Protection and Sustainability Strategies in China: Towards a Green Economy - Guo, Xiumei; Marinova, Dora (Palgrave Macmillan, 2014)
Due to its remarkable economic rise in the last three decades, China is now the world’s second largest economic power. The country however has also become the world’s largest greenhouse gases emitter and its growth continues to contribute to global and local environmental issues related to climate change, pollution, biodiversity loss and ecological deterioration. As China’s industrialisation, urbanisation and agricultural modernisation persist, developing a green energy saving economy is becoming more important for the country and the world. This chapter examines China’s major policies for environmental protection and current orientation towards a more sustainable development, including analysis of the relationship between GDP growth and carbon emissions. Sustainability strategies for policy makers are proposed to better direct the green growth path and achieve a secure clean energy future for an environmentally friendly society.